Pengaruh Implementasi Sistem Zonasi Terhadap Minat Belajar Murid: Analisis Deskriptif Kualitatif di Sekolah Dasar - Siswanto, Deny Hadi; Hanama, Akhmad (MURABBI, 2024)
This study aims to describe the implementation of the zoning system at Sitiharjo State Elementary School on students' learning interests. This study was conducted from July to August 2024 using a qualitative method with a purposive sampling technique. Data collection was carried out through observation, interviews, and documentation. The results of the study showed that: (1) the implementation of the zoning system has a positive effect on the feelings of happiness of students who live close to the school; (2) the effect of zoning on students' interest in learning activities is only felt at the beginning of learning, as seen from complaints from students who miss school after a long holiday and feel uncomfortable studying at home; (3) the implementation of the zoning system also affects students' attention to learning activities, as seen from their increased enthusiasm for learning at school by studying more conducively; (4) the zoning system affects student involvement as seen from their active participation in the learning process and group discussions